Criminological Scenarios of Crime Situation’s Transformation in the Context of Armed Conflict on Donbass in the Midterm - O. О. Titarenko (Law and Safety)
The article is focused on the study of crime transformation in Ukraine, depending on the probable course of the armed conflict on Donbass and the construction of criminological scenarios on its basis of changing its status. It has been noted that the construction of predictive criminological scenarios for changing the crime situation for the relevant time perspective is perspective for their use in the development of strategic program documents for the implementation of the state policy in the field of combating crime. To achieve this goal, the author of the paper has used appropriate methodological tools, which include: dialectical and general scientific methods of cognition (analysis, synthesis), as well as scripted methodology (expert and matrix approaches). It has been noted that the scriptural forecasting methodology is currently underused in domestic criminological research. It is considered relevant to understand the development of possible criminological scenarios of crime situation in Ukraine in terms of both changes in the course of the situation in the East of Ukraine, and taking into account the development of related problems in different spheres of public life (social, economic, political, military). Based on the use of scenario methodology, the author has formed six criminological scenarios (realistic, optimistic, negative – pessimistic) of the transformation of crime situation in the midterm (2019-2022). The author has expertly substantiated the highest probability of developing a crime situation in the midterm in the following three scenarios: “Stagnation and slight increase” (most realistic), “Control and security” (optimistic), “Turbulent crime” (negative). It has been proved that the development of probable criminological scenarios will depend on the intensity of external and internal threats to national security. Taking into account the available prognostic research in the military and political sphere and the results of own expert poll, we support the position of domestic experts that solution of the conflict on Donbass will remain in the stagnant form (“no war, no peace”) in the nearest future, which is going to affect the possibility of developing the most realistic and optimistic criminological scenarios.